Deep brain stimulation in the medial septum attenuates temporal lobe epilepsy via entrainment of hippocampal theta rhythm. (27th January 2021) - Wang, Ying; Shen, Yating; Cai, Xianhui; Yu, Jie; Chen, Cong; Tan, Bei; Tan, Na; Cheng, Heming; Fan, Xiang; Wu, Xiaohua; Liu, Jinggen; Wang, Shuang; et al.
Abstract: Aims: Temporal lobe epilepsy (TLE), often associated with cognitive impairment, is one of the most common types of medically refractory epilepsy. Deep brain stimulation (DBS) shows considerable promise for the treatment of TLE. However, the optimal stimulation targets and parameters of DBS to control seizures and related cognitive impairment are still not fully illustrated. Methods: In the present study, we evaluated the therapeutic potential of DBS in the medial septum (MS) on seizures and cognitive function in mouse acute and chronic epilepsy models. Results: We found that DBS in the MS alleviated the severity of seizure activities in both kainic acid‐induced acute seizure model and hippocampal‐kindled epilepsy model. DBS showed antiseizure effects with a wide window of effective stimulation frequencies. The antiseizure effects of DBS were mediated by the hippocampal theta rhythm, as atropine, which reversed the DBS‐induced augmentation of the hippocampal theta oscillation, abolished the antiseizure effects of DBS. Further, in the kainic acid‐induced chronic TLE model, DBS in the MS not only reduced spontaneous seizures, but also improved behavioral performance in novel object recognition. Conclusion: DBS in the MS is a promising approach to attenuate TLE probably through entrainment of the hippocampal theta rhythm, which may be therapeutically significant for refractory TLE treatment. Abstract : Here, we inferred that the DBS in the MS may be therapeutically significant for the treatment of refractory TLE. DBS in the MS not only alleviated seizures activities, but also improved behavioral performance in memory tests, via the enhancement of hippocampal theta rhythm.